The Dynamic Equilibrium of Hexakis(pentafluoroethyl)distannane Adducts [XSn(C2F5)3{Sn(C2F5)3}]− (X=Cl, Br, I, Sn(C2F5)3). Issue 17 (21st February 2018) - Wiesemann, Markus; Klösener, Johannes; Neumann, Beate; Stammler, Hans‐Georg; Hoge, Berthold
Abstract: The tin–tin bond cleavage of hexaorganodistannanes by nucleophiles is a long‐known reaction and widely used for stannate formation or stannyl group transfer. Herein, we detail our experiments to provide analytical evidence for the existence of the reasonably stable anionic complexes [XSn(C2 F5 )3 {Sn(C2 F5 )3 }] − (X=Cl, Br, I, Sn(C2 F5 )3 ) derived from hexakis(pentafluoroethyl)distannane. NMR investigations at low temperature lend further mechanistic insights. Thus, by detection of the imposing ion [Sn(C2 F5 )3 {Sn(C2 F5 )3 }2 ] −, one can surmise that the chemistry of Sn2 (C2 F5 )6 has more in common with the isolobal iodine than with classical distannanes. Abstract : Isolobal relationship : The introduction of electron‐withdrawing groups facilitates the NMR spectroscopic investigation of the stable complexes [XSn(C2 F5 )3 {Sn(C2 F5 )3 }] − (X=Cl, Br, I, Sn(C2 F5 )3 ) derived from hexakis(pentafluoroethyl)distannane. By detection of the trimeric ion [Sn(C2 F5 )3 {Sn(C2 F5 )3 }2 ] − one can surmise that the chemistry of Sn2 (C2 F5 )6 has more in common with the isolobal iodine than with classical distannanes (see Scheme; R=C2 F5 ).